1998
DOI: 10.1007/s002130050620
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low dose ketamine on sensory gating, neuroendocrine secretion and behavior in healthy human subjects

Abstract: Recently, much interest has been given to the role of glutamatergic N-methyl-D-aspartate receptors (NMDA) in sensory gating, such as prepulse inhibition (PPI) and reduction of the P50 evoked response potential (ERP). Currently, mainly animal data are available describing the role of NMDA receptors in these stimulus evaluation processes. Human data are virtually lacking and are potentially important, for instance for the understanding of sensory gating deficits observed in schizophrenia. Therefore, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
4
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 44 publications
9
69
4
1
Order By: Relevance
“…However, it has to be taken into account that these results contrast with most human studies, in which NMDAR antagonists either had no influence or even increased PPI van Berckel et al, 1998;Abel et al, 2003). Furthermore, we found group differences in the prepulse intensity dependence of the PPI.…”
Section: Habituation and Ppi Of The Startlecontrasting
confidence: 90%
See 1 more Smart Citation
“…However, it has to be taken into account that these results contrast with most human studies, in which NMDAR antagonists either had no influence or even increased PPI van Berckel et al, 1998;Abel et al, 2003). Furthermore, we found group differences in the prepulse intensity dependence of the PPI.…”
Section: Habituation and Ppi Of The Startlecontrasting
confidence: 90%
“…However, no effect of NMDAR antagonists on auditory gating was observed in a study in mice (Connolly et al, 2004). Furthermore, two studies in healthy human subjects showed no effect of ketamine on auditory gating (Oranje et al, 2002;van Berckel et al, 1998). The prominent auditory gating deficit in the NR1 mutants contrasts with the unaltered gating in several studies using acute pharmacological NMDAR blockade and possibly indicates that chronic deficient NMDAR-mediated signalling, perhaps even through development, has to be present to cause the auditory gating deficits.…”
Section: Auditory Gatingmentioning
confidence: 99%
“…41 With regard to PPI, specifically, the findings in healthy patients are mixed, with one study reporting disruption of 'PPI-like' auditory gating following treatment with ketamine, 42 some studies reporting no effects of ketamine on PPI, 43,44 and others reporting enhancement of PPI. [45][46][47] However, it is clear that patients with schizophrenia do have altered PPI 1,5,[48][49][50] and that in nonhuman primates 51,52 and rodents, [53][54][55][56] treatment with NMDA antagonists disrupts PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other NMDA antagonists, like PCP and ketamine, have been shown to induce an exacerbation of disease related psychotic symptoms in schizophrenic patients (Luby et al 1959(Luby et al , 1962Lahti et al 1995;Malhotra et al 1997aMalhotra et al , 1997b. The notion that D-cycloserine may be devoid of agonistic activity at NMDA receptors in this dose and design is supported by the lack of effect of D-cycloserine on LH secretion, as LH secretion in humans has been suggested to be sensitive to the agonistic effects of D-cycloserine (van Berckel et al 1998b) while it is not influenced by NMDA antagonists (van Berckel et al 1998a). Although D-cycloserine did not ameliorate schizophrenic symptoms in this study, the fact that they actually worsened suggests that NMDA systems may be involved in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%